Analisis Yuridis Hukuman bagi Pelaku Tindak Pidana Perdagangan Orang (Studi Kasus Putusan Nomor 1318 Pk/Pid.sus/2023) - Setyawan, Iwan; Simbolon, Winda C; Simanjuntak, Sarida Hotdeliana; Sembiring, Jenda Suranta (Universitas Medan Area, 2025)
Trafficking in persons is a transnational crime that violates human dignity and fundamental rights. This study analyzes the application of Law Number 21 of 2007 on the Eradication of Human Trafficking through a case study of Supreme Court Decision Number 1318 PK/Pid.Sus/2023. A normative juridical approach is employed to evaluate the legal grounds and judicial considerations in sentencing the perpetrator. The findings reveal that despite comprehensive legislation, its enforcement remains challenged by limited law enforcement capacity, evidentiary difficulties, and inadequate victim recovery mechanisms. The Supreme Court's ruling reflects legal consistency and rejects the judicial review due to the absence of valid new evidence (novum). This study recommends enhancing the capacity of legal practitioners and adopting a restorative justice approach to strengthen victim protection and improve sentencing effectiveness.